The reception of derivative images of the world axis archetype in the novels by M. Moorcock - Kosareva, Yuliya S. (Journal of the Belarusian State University. Philology, 2023)
On the example of novels «Daughter of the dream thief» and «The screling tree» by M. Moorcock, archetypical images and mythologems derived from the archetype of the world axis are considered. The degree of embodiment of this archetype in the works of the English writer and the level of the author’s reception are studied. Based on the analysis of the relationship between the groups of studied images (archetype, archetypical image, mythologeme), the concept of derivative image is introduced. So, for example, the archetypical images of the world tree and the world mountain, the mythologeme of the ash tree Yggdrasil or mount Olympus are images – derivatives of the prototype (archetype) of the world axis. Playing a key role in the organisation of the chronotope and the model of the world in mythology, they are also reflected in fiction. In particular, in the novels of science fiction writer M. Moorcock they occupy a central position, which indicates their significance and importance in the author’s world order. The novelty of the article lies in the study of the manifestations of archetypical images on the material of novels «Daughter of the dream thief» and «The screling tree» by M. Moorcock, since this problem has not been studied in the scientific space.
Keywords: archetype; archetypical image; derivative image; world tree; world axis; M. Moorcock; reception; fantasy